Network data envelopment analysis as instrument for evaluating water utilities’ performance - Norbaizura Kamarudin,; Wan Rosmanira Ismail,; Muhammad Azri Mohd, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Measuring the water sector performance is essential in improving the quality of water supply services. Commonly, many countries have used performance indicators to benchmark the efficiency and effectiveness of their water management. One of the important performance indicators in determining the efficiency of water utility is to look at their ability to reduce the Non-Revenue Water level or more commonly known as NRW. The percentage of NRW indicates the level of water leakage experienced and can also be classified as undesirable output in the water supply system. On the other hand, Data Envelopment Analysis (DEA) has been widely applied as the instrument to measure water sector performance, but only as a single process or so-called black-box analysis. Since the production of water supply services can be expressed as a two-stage network process, this study attempts to use the Network Data Envelopment Analysis (NDEA) to measure water sector performance. One of DEA model variations is Slack-based Measure (SBM) model, where is subsequently been expanded to the network structure (Network Slack-based Measure, NSBM). This study was undertaken to apply the NSBM model incorporating the undesirable outputs to measure the efficiency, then, proposed as a new performance indicator and can also be used for the benchmarking of the water utilities specifically for Malaysian water industry. From this study, not only the overall performance of each water utility, but also which process should be the focus for those inefficient water utilities can be determined.